Exploring Primiparous Mothers' Knowledge about Newborn Care: A Case Study - Wahyuni, Eko Sari; Retnowati, Lucia; Rahayu, Putri Meilina (Health Access Journal, 2026)
Maternal knowledge of essential newborn care is a key determinant of neonatal health, particularly among primiparous mothers who often experience limited preparedness and confidence in early caregiving. Understanding how educational interventions influence maternal knowledge and caregiving practices is important for strengthening maternal and neonatal health education. This study aimed to explore primiparous mothers’ knowledge of essential newborn care and to examine changes in knowledge and caregiving skills following an educational intervention. A qualitative descriptive case study design was used. Data were collected through in-depth interviews, questionnaires, and direct observations, and analyzed using thematic analysis to identify key themes before and after the intervention. Four themes emerged: knowledge and skills in newborn bathing, umbilical cord care, diaper changing, and awareness of exclusive breastfeeding. Before the intervention, limited knowledge and low confidence were observed across all themes. After the intervention, improvements were evident in knowledge and practical skills, particularly in umbilical cord care, diaper changing, and understanding of exclusive breastfeeding, while confidence in newborn bathing remained limited. Hands-on educational interventions can enhance primiparous mothers’ knowledge and caregiving skills, while sustained guidance and family involvement strengthen maternal confidence during early postpartum caregiving period